FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR KIMIA YANG TERDAPAT PADA BURSA EFEK INDONESIA - Widia Asri Nuraeni; Lilik Sri Hariani; Mochamad Fariz Irianto; Supami Wahyu Setiyowati (JURNAL AKUNTANSI, 2022)
This research aims to examine the effect of company fundamentals, capital structure, and interest rates on firm value in chemical sub-sector companies listed on the Indonesia Stock Exchange. The research method uses quantitative methods with multiple linear regression models. The research was conducted on chemical sub-sector companies using financial statements. The sampling method used purposive sampling. The variables studied were company fundamentals, capital structure, interest rates, and firm value. The results of this research show that simultaneously the company's fundamental variables, capital structure, and interest rates affect the value of the company. On the other hand, partially the company's fundamental variables and capital structure have a positive effect on firm value in chemical sub-sector companies listed on the IDX. On the other hand, partially the interest rate has a negative effect on firm value in chemical sub-sector companies listed on the IDX.